Melasma update - Rashmi Sarkar; Pooja Arora; Vijay Kumar Garg; Sidharth Sonthalia; Narendra Gokhale (Wolters Kluwer Medknow Publications, 2014)
Melasma is an acquired pigmentary disorder characterized by symmetrical hyperpigmented macules on the face. Its pathogenesis is complex and involves the interplay of various factors such as genetic predisposition, ultraviolet radiation, hormonal factors, and drugs. An insight into the pathogenesis is important to devise treatment modalities that accurately target the disease process and prevent relapses. Hydroquinone remains the gold standard of treatment though many newer drugs, especially plant extracts, have been developed in the last few years. In this article, we review the pathogenetic factors involved in melasma. We also describe the newer treatment options available and their efficacy. We carried out a PubMed search using the following terms "melasma, pathogenesis, etiology, diagnosis, treatment" and have included data of the last few years.